LABORATORY STUDY OF STRENGTH CHARACTERISTICS GLASS-FIBER REINFORCED LIGHT-CURED COMPOSITE - O. A. Udod; O. O. Pompiy (Ukrainian Medical Stomatological Academy, 2019)
Abstract. Resin-bonded bridges (RBB), which are made by the direct method are widely used to restore the integrity of the dentition. There is no common opinion regarding the optimal design of the retention elements of such prosthetics. Purpose is to study the influence of the design RBB supporting elements on the mechanical strength of fixing light-cured composite material, reinforced with glass-fiber tape and bulk, to the hard tissues of the teeth in laboratory conditions,. Materials and methods. The study was conducted on 20 laboratory samples. Extracted intact lower third molars were sprayed into halves in a transverse direction on two fragments. Each of the fragments was fixed in fast-hardening plastic so that the contact surface of the fragment of the removed tooth stood 2 mm above the plastic level, with the surface of the enamel, which was a circle, with a diameter of 4-5 mm, and was free. Samples were divided into 2 groups of 10 in each. In samples of group I, the preparation of an approximate surface of a tooth fragment was made in the form of a box-shaped cavity with rounded corners and a minimal conicality of vertical walls with the following parameters: length - 3 mm, width - 3 mm, depth - 2 mm. Reference cavities in the samples of the second group were prepared according to the proposed method, after preparation of the classical box-shaped cavity with parameters: length - 3 mm, width - 3 mm, depth - 2 mm, created additional retention elements in the form of dives located in the lower third each of the vertical walls of the cavities using special marking burs with height and thickness of the working part by 1 mm. In order to determine the strength of the light-cured composite fixation, reinforced by glass-fiber tape and bulk, developed device for investigating the maximum destructive loading of the samples by the shear method was used. The destructive load was measured using a dynamometer installed in the test vehicle to within 0.1 N. In addition, the specific strength of the samples was determined as the ratio of the destructive load to the surface area of the fracture or separation, and the safety margin, as the ratio of the destructive load to the mean the value of the chewing load in the area of molars taken for 150 N. Results and discussion. During conducting ofd the laboratory study of fixation strength of light-cured composite, reinforced by glass-fiber tape and bulk, to solid teeth tissues with different design retention elements there were found that the maximum destructive load and specific strength of the different sample groups were significantly different (p <0,01). Indicators of destructive loading of samples of the 1st group were ranged from 576.5 N to 835.9 N and amounted to an average of 771.8+90.1 N. At the same time, the destructive loading for samples of the II group was from 2425.0 N to 2999.0 N with an average of 2805.9+191.4 N. Thus, the samples of the second group had almost 4 times the magnitude of the maximum destructive load than the values of group І samples. The indexes of the specific strength of light-cured composite fixing to the hard tissues of the supporting teeth were also higher in the samples of the second group, their values were ​​ranged from 341.1 N / mm2 to 421.8 N / mm2 with an average value of 394.5+26.8 N/mm2. In samples from Group I, these figures were ranged from 23.1 N/mm2 to 33.4 N/mm2 and amounted to 28.6+3.3 N/mm2 on average, they were 14 times smaller than II group indicators. Conclusion. As a result of the laboratory study, it was found that samples of the second group with the proposed design of retention elements had higher characteristics of the strength of fixation to the hard teeth tissues than those of group I with the "classic" box-shaped form of retention cavities. Destruction of samples of the second group occurred at a significant load that greatly exceeded that which occured in clinical conditions and at a distance from the retention elements, created according to the proposed design, due to insufficient physical and mechanical parameters of the light-cured composite and reinforcing fiberglass elements. The use of the proposed preparation option will reduce the risk of failure of the fixation and improve the prognosis for the long-term exploitation of resin-bonded bridges made by direct method.